Aktivitas Lansia, Kualitas Hidup HUBUNGAN AKTIVITAS SOSIAL LANSIA TERHADAP KUALITAS HIDUP DI PESISIR RW 03 KELURAHAN KEDUNG COWEK SURABAYA - Dya Sustrami (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2017)
Abstract The process of aging resulted in physical, social, and psychological changes that can affect the quality of life of the elderly. This study aims to determine the relationship of social activities of the elderly to the quality of life in coastal RW 03 Kedung Cowek Surabaya Village. This research is an analytical study with Cross Sectional design. The number of samples is 32 respondents taken with simple random sampling. Data analysis using Spearman correlation test. There is a social activity relationship to the quality of life of 0,000 (? <0.05). The implication of this research, needed support from family and related institution in developing elderly activity to improve quality of life. Keywords: Social Activity, Quality of Elderly Life